2022
DOI: 10.1136/fmch-2021-001515
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners’ (GPs) experience, attitudes and needs on clinical genetic services: a systematic review

Abstract: ObjectiveThe proliferation and growing demands of genetic testing are anticipated to revolutionise medical practice. As gatekeepers of healthcare systems, general practitioners (GPs) are expected to play a critical role in the provision of clinical genetic services. This paper aims to review existing literature on GPs’ experience, attitudes and needs towards clinical genetic services.DesignA systematic mixed studies review of papers published between 2010 and 2022.Eligibility criteriaThe inclusion criterion wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 89 publications
(347 reference statements)
0
5
0
Order By: Relevance
“…Our assessment of behavioural change was halted by low GP recruitment for the interview 6 months after completion of the module. This may have been due to busy GPs' perceived lack of time to schedule and complete an interview rather than a survey (Brodaty et al, 2013), a lack of perceived value in participating further in research without additional professional development (Brodaty et al, 2013) or a rarity of genetic cases to practise what they had learnt between surveys and interview (Ong et al, 2022). Evidence for improved clinical practice after a medical genomics education intervention is scant in the literature (Paneque et al, 2016;Talwar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our assessment of behavioural change was halted by low GP recruitment for the interview 6 months after completion of the module. This may have been due to busy GPs' perceived lack of time to schedule and complete an interview rather than a survey (Brodaty et al, 2013), a lack of perceived value in participating further in research without additional professional development (Brodaty et al, 2013) or a rarity of genetic cases to practise what they had learnt between surveys and interview (Ong et al, 2022). Evidence for improved clinical practice after a medical genomics education intervention is scant in the literature (Paneque et al, 2016;Talwar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, future research may benefit from the new roles for Australian GPs in genetic carrier screening (Delatycki et al, 2019), providing additional incentive for GPs to undertake genomics education and participate in its evaluation. Longer-term research with GPs may also be facilitated through additional communication and/or offering additional education updates as part of any follow-up (Ong et al, 2022) to increase the perceived value of the GPs' participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having a comprehensive knowledge of common psychiatric drugs is paramount when properly interpreting PGx testing information to ensure patient safety and avoid ADRs from drug-drug interactions. A recent review by Ong et al (2022) investigated the experience, attitudes, and knowledge of GPs towards the application of PGx in primary practice and found that whilst most GPs understood the basic principles and recognised the potential benefits of using PGx testing, many were uncertain about how to use genetic testing to inform treatment decisions. This was further supported in recent findings, where the implementation of PGx education and training efforts were shown to improve the comfort felt by primary care providers, such as GPs, when ordering a PGx test for their patients ( Preys et al, 2023 ).…”
Section: Clinical Application Of Pharmacogenetics In Youth Mental Healthmentioning
confidence: 99%
“…Although the studies above illustrate a keen understanding on the usefulness for PGx testing in the primary care setting, with no endorsed guidelines on the use of PGx testing in clinical practice, many GPs have expressed the need for further research that explores the translation of new genetic technologies into clinical practice to help inform the development of such guidelines. The review by Ong et al (2022) emphasised the importance of gathering a complete understanding of the experiences, knowledge, and attitudes held by GPs towards genetic testing. Gathering this information and tailoring the integration of PGx testing to the requirements of primary care providers is integral for successful adoption into clinical practice ( Aboelbaha et al, 2023 ).…”
Section: Clinical Application Of Pharmacogenetics In Youth Mental Healthmentioning
confidence: 99%